Effective Communication: Any Role in Classroom Teaching - Learning Process in Nigerian Schools? - C.O. Fashiku (University of Sofia, 2017)
The place of effective communication is so central and indispensable in the classroom teaching and learning process. Teacher in the classroom requires effective communication skills in marshaling his/her points before learning that could lead to the attainment of educational aims and objectives in the school can take place. In this presentation, the following were discussed among others; the concept of teaching, the concept of learning, internal and external factors in the child's growth and development, the concept of communication and communication process in the classroom, the channels and styles of communication, nonverbal, visual communication, communication and classroom teaching skills, communication barriers and solutions to barriers to effective communication in the classroom. It was concluded and recommended that teachers' should therefore try as much as possible to reduce impediments tagged 'communication barriers' by complying with the discussed classroom communication skills in order to ensure the goal attainment of teaching- learning in schools in Nigeria.